2003
DOI: 10.4315/0362-028x-66.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Interlaboratory Validation of a Selective Agar for Phosphatidylinositol-Specific Phospholipase C Activity Using a Chromogenic Substrate To Detect Listeria monocytogenes from Foods

Abstract: Phosphatidylinositol-specific phospholipase C (PI-PLC) activity is a potential virulence factor and is exhibited only by the Listeria species Listeria monocytogenes and Listeria ivanovii. A chromogenic substrate for the direct detection of PI-PLC activity is available in a new medium (BCM L. monocytogenes plating agar). The use of a chromogenic substrate offers a mechanism with which to directly screen for L. monocytogenes and L. ivanovii other than the esculin used in Oxford (OXF) and Palcam (PAL) agars, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…by revealing esculinase (b-glucosidase) activity, a metabolic enzyme common to all Listeria species, but do not distinguish L. monocytogenes from other species (Leclercq, 2004). Typical colonies are selected from these selective differential agars and submitted to further biochemical tests and hemolytic activity to determine the identity of the species (Jinneman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…by revealing esculinase (b-glucosidase) activity, a metabolic enzyme common to all Listeria species, but do not distinguish L. monocytogenes from other species (Leclercq, 2004). Typical colonies are selected from these selective differential agars and submitted to further biochemical tests and hemolytic activity to determine the identity of the species (Jinneman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Listeria is composed by six species, with Listeria monocytogenes being the only significant human pathogen (Jinneman et al, 2003). L. monocytogenes is responsible for sporadic cases and outbreaks of listeriosis associated with a variety of foods, including meat products, raw vegetables and dairy products (Leclercq, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that ALOA compares favourably with Oxford agar for the recovery of L. monocytogenes (Vlaemynck et al. 2000; Jinneman et al. 2003; Sacchetti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of chromogenic media for the isolation of L. monocytogenes have been reported previously (Jinneman et al. 2003; Sacchetti et al.…”
Section: Introductionmentioning
confidence: 99%